Tick species, tick-borne pathogen distribution and risk factor analysis in border areas of China, Russia and North Korea - Min, Pengfei; Song, Jianchen; Zhao, Shaowei; Ma, Zhen; Meng, Yinbiao; Tang, Zeyu; Wang, Zhenyu; Lin, Sicheng; Zhao, Fanglin; Liu, Meng; Wang, Longsheng; Jia, Lijun (Frontiers in Veterinary Science, 2025)
IntroductionTicks are important ectoparasites of livestock. Ticks and tick-borne diseases (TBDs) cause losses to the animal husbandry industry and also present a major hidden danger to public health and safety. However, the tick species and prevalence of TBDs in border regions of China, Russia, and North Korea remain unknown. The purpose of this study was to identify the tick species and tick-borne pathogens endemic in these regions.MethodsMorphological and molecular identification of ticks was performed by microscopy and polymerase chain reaction (PCR), and the distribution of tick species, pathogen, and risk factors of infection were analyzed.ResultsIn total, 1,187 ticks were collected from the border areas of 13 localities in eight cities. Five tick species were identified: Haemaphysalis longicornis (39.68%), Ixodes persulcatus (25.36%), Haemaphysalis japonica (15.50%), Dermacentor silvarum (15.42%), and Haemaphysalis concinna (4.04%). There were more female than male ticks, and nymphs were the least frequently collected. I. persulcatus was the main species in the forest environment, while H. longicornis was the main species in grasslands and animal surface. Four pathogens were detected: Rickettsia, Bartonella, Anaplasma, and Babesia.DiscussionPathogen detection in ticks differed significantly among the environments and between Sexes. There were significant differences in the proportion of ticks infected with Rickettsia, Bartonella, Anaplasma, and Babesia among regions, species, sexes, and environments. The results of this survey of the tick species in border areas of China, Russia, and North Korea provided a scientific basis for the prevention and control of TBDs.